2016
DOI: 10.1007/s40268-016-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparative Bioavailability of a Novel Three-Dimensional Printed Fast-Melt Formulation of Levetiracetam Following the Administration of a Single 1000-mg Dose to Healthy Human Volunteers Under Fasting and Fed Conditions

Abstract: BackgroundRapidly disintegrating or ‘fast-melt’ oral formulations have been developed recently to facilitate drug intake among patients. Even though these formulations have helped to improve therapy adherence, some of their limitations include: the dissolution time, their facility to be swallowed, and the dosage strengths that may be accommodated. To overcome these limitations, a novel, porous, quickly disintegrating, and easier-to-swallow fast-melt formulation based on powder-liquid, three-dimensional printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Hence, it deals with a dosage form produced on a large-scale and approved via the regulatory procedure currently in use. A recent study also demonstrated bioequivalence of this product in the fasted state to the conventionally fabricated immediate-release tablets available on the market 80 .…”
Section: Regulatory Perspectivesmentioning
confidence: 75%
“…Hence, it deals with a dosage form produced on a large-scale and approved via the regulatory procedure currently in use. A recent study also demonstrated bioequivalence of this product in the fasted state to the conventionally fabricated immediate-release tablets available on the market 80 .…”
Section: Regulatory Perspectivesmentioning
confidence: 75%
“…High porosity also characterises Spritam®, the first medicine fabricated through a 3D printing process-known as ZipDose®-to gain Food and Drug Administration approval in 2015, marketed by Aprecia Pharmaceuticals [25]. Spri-tam® is an antiseizure drug containing the active ingredient levetiracetam and the rationale behind its development is that the highly porous structure allows the tablet to disintegrate in a mean of 11 s, allowing a fast onset of action [26,27].…”
Section: Powder Bed-inkjet 3d Printingmentioning
confidence: 99%
“…35 Drug conjugation to powder has been used to create 3D printed drugs, such as levetiracetam. 36 3DP allows for control of spatial drug distribution and accurate drug dispense at low volumes, thereby reducing waste in manufacturing drugs and creating a highly tunable release profile. 37,38 ECM powders have not been used in drug 3DP, but their separate uses in drug delivery and 3DP indicates potential future application in drug 3DP.…”
Section: Drug Deliverymentioning
confidence: 99%